PENGARUH JARAK KERENGGANGAN ELEKTRODA BUSI TERHADAP KONSUMSI BAHAN BAKAR PADA MOTOR BENSIN MEREK TOYOTA 5 K KIJANG - Wibowo, Agus; Hidayat, Tofik; Abadi, Moh. Yusuf (ENGINEERING, 2010)
One part of car producinginq moving power is called as an engine. The type of engine used in most cars is reciprocating piston and. 9 intenal combustion engine can. The internal combustion engine can be divided into (1) gasoline motor, which its mixing process between air and fuer takes place in the carburator and transfried into ttu cylinder. These mixed substsnces are pressed by the reciprocating piston and burned to produce power (2) Diesel motor which only the air is entered into the cyrinder, then, after the air is presed by the reciprocating piston, diesel fuel is injected in the cylinder using fuel injector systern that enables the combustion and the expansion for producing power.Reciprocating piston gasorine motor is one of the basic power plants, which is the widely used today for moving the this reciprocating piston gasoline molor change the het energy energy to mechanical energy which is gained by fuet combustion in that engine. one of the combustion proccsses in that engine is igniting process. This paper discuses about theinfluence of spark plug elektroda gap adjustment. The experimental result conducted on the Toyota Kijang 5K engine show ,that spark plug elektode gap influences spark resulted for igniting fuel and air mixture and the most ideal gap is 0.8 mm which resurlt in the best combustion process. Therefore it can be concluted that this gap resurlt. The most eficient fuel consumption.Keywords: gasoline motor, spark plug electrode , fuel consumption.